PEMBERDAYAAN MASYARAKAT DESA MELALUI PROGRAM KULIAH KERJA MAHASISWA: STUDI KASUS DESA CIBODAS, KECAMATAN BOJONG GENTENG, KABUPATEN SUKABUMI - Gerry Rizky Andrean Supit (STISIP Widyapuri Mandiri Sukabumi, 2025)
The Community Service Program (Kuliah Kerja Mahasiswa / KKM) is a form of implementing the Tri Dharma of Higher Education, particularly in the aspect of community engagement. KKM Group 04 was carried out in Cibodas Village, Bojong Genteng District, Sukabumi Regency, from August 5 to 30, 2025, with the aim of raising community awareness in the fields of education, health, environment, and local economic empowerment. The methods employed included observation, interviews, and active participation in community activities. The core programs included the construction of a Rocket Stove as a sustainable waste management facility, installation of waste-sorting education boards, renovation of public trash bins, and support for micro, small, and medium enterprises (MSMEs) through the issuance of a Business Identification Number (NIB), logo design, and promotional banners. Supporting programs involved educational activities in schools (digital literacy, anti-bullying campaigns, English lessons), community health programs such as GELI BUMILA, posyandu (integrated health services), group exercise sessions, as well as socio-cultural activities including the commemoration of Indonesia’s 80th Independence Day. The results indicated an increase in community awareness of clean and healthy living behaviors, strengthened legal and branding identity for MSMEs, and positive collaboration between students, village officials, and the local community. For students, this program provided real-life experience in community empowerment while enhancing social and leadership skills.